Pretend play as the space for development of self-regulation: cultural-historical perspective - Bredikyte, Milda; Brandisauskiene, Agne (Frontiers in Psychology, 2023)
Self-regulated behavior is a prerequisite for learning and success in life. Considerable research confirms that mature forms of play support the development of self-regulation in the early years. This study explores the relationship between (3–6-year-olds) children’s pretend play and self-regulation skills. Teachers filled out a child’s play and self-regulation checklist evaluating the level of children’s play and self-regulation skills. The findings revealed that the levels of children’s play and self-regulation skills are statistically significantly linked: the better the child performs an assumed role in play activity, the higher the level of their self-regulation. The results also suggest that a child’s playing skills, gender, and age predict children’s self-regulation skills manifested in play activity.